Influence of nature on spirituality and cognition: an examination of short-term exposure through video clips - Hayashi, Takechika; Nomura, Michio (Frontiers in Psychology, 2025)
IntroductionNature exerts a significant impact on spiritual experiences. While extended interactions with nature ranging from living in nature-rich neighborhoods to hiking through mountains for some time, have been found to promote spirituality and religiosity among individuals less is known about how its dual aspects (beautiful vs. threatening) and trait (dispositional) spirituality interact to shape these effects.MethodsIn a controlled laboratory study, 57 Japanese university students (Mage = 21.46 ± 2.60, 61.4% men) were exposed to natural scenes with contrasting emotional tones (positive and threatening) and completed self-report measures of spirituality and cognitive transformation alongside implicit association tests.ResultsResults indicated that watching nature scenes promoted spiritual feelings and induced cognitive shifts in perceptions of self-size, time availability, and self-transcendence. Notably, participants viewing positive nature scenes reported higher spirituality scores than those exposed to threatening scenes. Crucially, trait spirituality emerged as a significant moderator; individuals with higher dispositional spirituality exhibited a more pronounced increase in state-level spirituality in both nature conditions compared to a neutral baseline.DiscussionThese findings provide empirical support for theoretical perspectives suggesting that both positive and even adverse natural experiences, such as natural disasters, can enhance spiritual awareness by amplifying momentary shifts. The study underscores the importance of considering the dual aspects of nature when examining spiritual experiences and highlights the interplay between state and trait spirituality. These findings also underscore the need for more nuanced research on environmental influences on spiritual identity.